Quality Evaluation and Storage Study of Chicken Meat Pickle - Rajbanshi, Sunil; Adhikari, Bhaskar Mani; Subba, Dilip (Journal of Food Science and Technology Nepal, 2016)
A study was undertaken to develop shelf stable intermediate moisture type chicken meat pickle and evaluate its quality and storage stability. Pre-cooked and fried lean minced chicken meat was mixed with salt, spices and vinegar and packed air tight in glass jar. The product had appreciable sensory quality and low total microbial, yeast and mould counts. Salmonella, Staphylococci and E. coli were found absent in the product. Microbial count and peroxide value lay within the acceptable levels for sixty days.